DYNAMICS OF THE RELATIONSHIP BETWEEN GENERAL PHYSICAL FITNESS AND SPECIFIC PERFORMANCE INDICATORS OF YOUNG BOXERS DURING PRE-COMPETITION TRAINING (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article is devoted to studying the dynamics of the relationship between general physical fitness and specific performance indicators of young boxers during pre-competition training. The study analyzes changes in the physical condition, endurance, speed, and specific technical skills of young athletes in the pre-competition period. The results demonstrate the impact of general physical fitness on specific performance and their correlation with competition outcomes. The study provides practical recommendations for optimizing the training process of young boxers.